Characteristics and utilization of black soils in Indonesia - Sulaeman, Yiyi; Sukarman, Sukarman; Neswati, Risma; Nurdin, Nurdin; Basuki, Tony (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Black soils store a high amount of soil organic carbon (SOC) and play a crucial role in climate change, food security, and land degradation neutrality. However, data and information regarding black soils in tropical regions, including Indonesia, are limited. This study aimed to characterize and identify the utilization of black soils in Indonesia based on legacy soil survey data.  We collated 142 soil pedon samples of Mollisols from articles, technical reports, and existing datasets. The site information (site position, elevation, land use type, parent material) and selected physicochemical properties were stored in a spreadsheet, from which exploratory data analysis was conducted.  The result showed that the median SOC content was 1.53%, ranging from 0.6 to 8.2 %; cation exchange capacity was 30 cmol kg-1, ranging from 9 to 95 cmol kg-1; base saturation was 87%, ranging from 11 to 100 %; and bulk density was 1.21 g cm-3, ranging from 1.13 to 1.36 g cm-3. Other soil characteristics (particle size distribution, exchangeable bases, pH, pore, and water retention) varied with horizon type and land use/land cover. The black soils have been used for paddy fields, dryland farming, and gardens with low management intensity. Main cultivated crops include rice (Oryza sativa), corn (Zea mays), cassava (Manihot esculenta), sweet potato (Ipomoea batatas), and nutmeg (Myristica fragrans), clove (Syzygium aromaticum), coconut (Cocos nucifera), and cocoa (Theobroma cocoa).  Threats to black soil functions include soil erosion, carbon loss, and nutrient imbalance. Soil and water conservation measures, integrated soil nutrient management, and agroforestry are among the best land management practices for black soils.